(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of the study is to determine the Role of NC II Qualifications in Selected BSHM Graduating Students Towards Professional Development, analyze the number of NC II taken by the respondents, the importance of NC II, and the problems they have encountered. The results of this study reveal that most of the graduating BSHM students in Bestlink College of the Philippines are at the age of 22 years old, mostly male with 56 percent, followed by 44 percent female students, all are single, and either a 3 NC II holders, 2 or 1 and some may have non. Most find NC II as a very important tool in terms of their skills, competencies, employment opportunities, and knowledge. Also, students agree that they have problems encountered in terms of finances, time availability, and contentment. Based on the gathered data and conclusions drawn, this study is recommended to the students, program head and teachers, parents, and all learners. Students should know that taking NC II has lots of benefits to offer for their future profession; program heads and teachers should assess students more with their learning and improvements regarding their skills and knowledge. Lastly, parents should proudly support their children with their chosen career or education.